Multiple electronic state mechanism for carboryne reaction with benzene: A DFT study. Issue 12 (7th March 2017) - Huo, Rui‐Ping; Guo, Li‐hui; Zhang, Fu‐qiang; Zhang, Xiang
Abstract : The multiple electronic state mechanisms of the reaction of carboryne with benzene were investigated by M11 calculations. Mechanisms leading to [4 + 2] cycloaddition product P4 + 2, [2 + 2] cycloaddition product P 2 + 2, CC insert product P C‐Cins and CH insert product P C‐Hins were considered. The barrier/stability to structural characteristics correlations revealed that, 1) [2 + 2] addition is a two‐step mechanism which exhibits three electronic state reactivity, and both the addition steps are controlled by the barriers on open‐shell singlet (OSS) potential energy surface (PES); 2) [4 + 2] product P 4 + 2 is a kinetic product on the experimental condition, and other products should be obtained under more harsher condition. The theoretical results well explain the experimental facts. Abstract : In the reaction with benzene, carboryne can play four roles: formal bonding role leads to P 4 + 2 ; its singlet biradical form, triplet biradical form and singlet zwitterionic form yield the [2 + 2] product P 2 + 2, CC insert product P C‐Cins, and CH insert product P C‐Hins, respectively. P 4 + 2 is the kinetically favorite product but P C‐Hins is thermodynamically more stable.